If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + 6) = 2(5x) Reorder the terms: 2(6 + 3x) = 2(5x) (6 * 2 + 3x * 2) = 2(5x) (12 + 6x) = 2(5x) Remove parenthesis around (5x) 12 + 6x = 2 * 5x Multiply 2 * 5 12 + 6x = 10x Solving 12 + 6x = 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 12 + 6x + -10x = 10x + -10x Combine like terms: 6x + -10x = -4x 12 + -4x = 10x + -10x Combine like terms: 10x + -10x = 0 12 + -4x = 0 Add '-12' to each side of the equation. 12 + -12 + -4x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 0 + -12 -4x = 0 + -12 Combine like terms: 0 + -12 = -12 -4x = -12 Divide each side by '-4'. x = 3 Simplifying x = 3
| d/-6=-4 | | b+8=6 | | n+9=-1 | | B=(7-3x)(2x-3) | | k/-5=-7 | | 16=t+5 | | w+9=21 | | 6m=36 | | -3d=-24 | | -3w=33 | | a-3=-1 | | 3+d=14 | | a+7=12 | | -3+w=-6 | | 2b=-2 | | -7w=-63 | | -5a=-45 | | n+7=9 | | 5w-41=-6(w-6) | | k+6=0 | | w/-5=-3 | | 3x+205=11x-11 | | 5x-41=-6(w-6) | | 8x13/4 | | -8(v+4)=-3v+13 | | -12x^2+10x+17=0 | | -8(v+4)=3v+13 | | 6x-3y=4bx | | 6v-41=-5(v+6) | | x-16-3/4=8 | | 2x-(x-5)/2=14 | | 2x-x-5/2=14 |